1999
DOI: 10.2307/3496574
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Selected Insecticides to Fall Armyworms (Lepidoptera: Noctuidae) in Laboratory Bioassay Studies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Florida Entomological Society is collaborating with JSTOR to digitize, preserve and extend access to The Florida Entomologist. ABSTRACTEfficacy of conventional and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 12 publications
1
22
2
1
Order By: Relevance
“…While, methomyl was the fourth one, its LC 50 value was 562.073 ppm after 24 hrs. These results are in agreement with those obtained by Adamczyk et al (1999), they reported that novel insecticides chlorfenapyr, methoxyfenozide, spinosad and tebufenozide were more toxic than conventional insecticide thiodicarb toward the third instar larvae of fall armyworm, S. frugiperda using diet bioassay. Moreover, Argentine et al (2002) found that the emamectin benzoate was consistently the most toxic insecticide; it was 20-to 64.240-times more toxic than chlorfenapyr, fipronil and tebufenozide.…”
Section: Resultssupporting
confidence: 92%
“…While, methomyl was the fourth one, its LC 50 value was 562.073 ppm after 24 hrs. These results are in agreement with those obtained by Adamczyk et al (1999), they reported that novel insecticides chlorfenapyr, methoxyfenozide, spinosad and tebufenozide were more toxic than conventional insecticide thiodicarb toward the third instar larvae of fall armyworm, S. frugiperda using diet bioassay. Moreover, Argentine et al (2002) found that the emamectin benzoate was consistently the most toxic insecticide; it was 20-to 64.240-times more toxic than chlorfenapyr, fipronil and tebufenozide.…”
Section: Resultssupporting
confidence: 92%
“…Hence control with contact insecticides is often ineffective though it remains until today the most widely practiced management measure. Its frequent overuse has led to the emergence of regional populations resistant to several classes of pesticides [15] and favoured the use of transgenic Bt-maize. Thus, cultivars expressing the Cry1F toxin against insect defoliators are currently widely commercialized in the western hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, larvae usually bore into corn whorls or ears and develop under protected conditions, which allows them to avoid direct exposure to insecticides. This greatly increases the chance of survival for S. frugiperda during insecticidal sprays and low‐dose exposure to insecticides probably has contributed to their resistance to several classes of insecticides (Adamczyk et al ., ; Gutiérrez‐Moreno et al ., ).…”
Section: Discussionmentioning
confidence: 99%